Treating recurrent hemarthrosis after knee arthroplasty with selective embolization: a cohort study of 56 patients - Suvi-Maria Sirola; Juuso Heikkinen; Pekka Kerimaa; Juho Kariniemi; Tuukka Niinimäki (Acta Orthopaedica)
Background and purpose: Recurrent hemarthrosis (RH) is a rare late complication of knee arthroplasty, with an unknown etiology. We aimed to evaluate the effectiveness of arterial embolization (AE) on resolution of hemarthrosis following knee arthroplasty. Additionally, we investigated pain management requirements after the procedure and related complications. Methods: 56 patients underwent AE for recurrent hemarthrosis between 2015 and 2023. The prevalence of hemarthrosis was 0.6%. The median age of the patients was 70 years (range 42–88), with 41 females and 15 males. 70 embolizations were performed, consisting of 56 initial procedures and 14 repeat procedures. Clinical success was defined as the resolution of hemarthroses. Results: Technical success was achieved in 93% of cases. Clinical success improved from 64% to 79% after the second treatment; subsequent sessions did not yield further improvement. 12 patients (21%) required 1 or more reoperations. The majority of patients (86%) relied solely on analgesics for post-treatment pain management. Complications occurred in 7% of treatments, most of which resolved spontaneously. Conclusion: AE is effective in the treatment of recurrent hemarthrosis but 21% had reoccurance. Oral analgesics are generally sufficient for managing post-embolization pain. 7% had complications.